Development of Professional Ethics Curriculum in the Operating Room for the Current Era of Surgery: A Mixed Method Study - Sadati, Leila; Motaharipour, Morteza; Younas, Ayesha; Farajidana, Hoorvash; Hosseini, Fakhrolsadat; Abjar, Rana (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2023)
Introduction: The rapid advancement of intricate technologies and the emergence of novel surgical methodologies necessitate nuanced ethical decision-making under high-stress scenarios. Consequently, cultivating an understanding of professional ethics within the surgical environment is crucial for all practitioners involved in patient care. This study was initiated with the aim of designing a comprehensive curriculum for Iranian medical schools, focusing on professional ethics within the operating room. Methods: This mixed-method exploratory research was executed in distinct qualitative and quantitative phases. The first stage involved conducting 12 structured interviews with Iranian faculty members who were experts in education of professional ethics and operating room staffs for assessing the current needs and reviewing extant curricula. The subsequent quantitative phase entailed evaluating the elements of each curriculum axis via the Delphi method. Results: The qualitative phase led to the identification of 45 primary codes, 14 subcategories, and 5 primary categories. The quantitative phase confirmed 3 instructional goal domains, 12 instructional content areas, 8 teaching methodologies, and 10 evaluation methods through the Delphi process. These confirmed components were eventually incorporated into various theoretical and clinical courses as longitudinal integration themes. Conclusion: Based on our findings, we recommend the development of educational objectives targeting cognitive, affective, and psychomotor domains and the longitudinal integration of a professional ethics course.